Kinetic Modeling of Methylcyclohexane Dehydrogenation Reaction for Toluene Production in the Polymer Industry - Muhammad Fadhillah Ansyari; Fitria Ika Aryanti (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Toluene, also known as methylbenzene, plays an important role in various industries, particularly the polymer industry where it is used as a solvent, an adhesive in resins and an additive in rubber and cosmetic products. However, the current production of toluene in Indonesia is insufficient to meet the growing demand, particularly in the polymer sector, prompting the exploration of alternative production methods. This work investigates the production of toluene through the dehydrogenation of methylcyclohexane (MCH) using a Pt/Al₂O₃ catalyst, a process that also generates hydrogen, contributing to clean energy initiatives. The research focuses on identifying the optimal kinetic model for the dehydrogenation reaction, taking into account reactor design and catalyst performance. Four kinetic models were analysed using Polymath software, with the second model highlighting methylcyclohexane adsorption as the key factor and showing the best agreement with experimental data. The results indicate that toluene production can be improved using a fixed bed reactor and Pt/Al₂O₃ catalyst, with surface reactions as the rate-limiting step, offering promising prospects for meeting the needs of the polymer industry.